Bimbingan Teknis Implementasi Perizinan Berusaha Berbasis Risiko Melalui OSS-RBA di DPMPTSP Kabupaten Bantul - Wiyunnita; Astuti, Eka Dyah Ayu; Rochmadi, Tri (Darma Abdi Karya, 2024)
Implementing the risk-based business licensing system or OSS-risk-based approach (OSS-RBA) is an innovative step in government administration that will improve efficiency, transparency, and openness in the business licensing process in Indonesia. This licensing system is useful for facilitating business actors in issuing business licenses. This study uses a descriptive qualitative method that makes the Bantul Regency Investment and One-Stop Integrated Service Office (DPMPTSP) as the object. This study aims to determine the implementation of the OSS-RBA Policy, Factors that inhibit the implementation of OSS-RBA, and Efforts made to overcome Obstacles in implementing OSS-RBA by the Bantul Regency DPMPTSP. The findings that researchers found during the study were that OSS-RBA was very helpful for people who experienced obstacles with distance problems so that they could not come to the DPMPTSP to take care of permits and researchers also found people who were not fully aware of the existence of this OSS-RBA policy. Based on the research that has been conducted, the author concludes that the implementation of the OSS-RBA policy provides benefits to the community, especially those who are or live far from DPMPTSP, and is very helpful for people who cannot come to DPMPTSP. The author's suggestion to DPMPTSP Bantul Regency is to optimize widespread socialization, overcome internet network obstacles, and improve the quality of human resources to maximize services from the OSS-RBA policy.